2018
DOI: 10.4102/abc.v48i1.2345
|View full text |Cite
|
Sign up to set email alerts
|

Invasive potential and management of naturalised ornamentals across an urban environmental gradient with a focus on Centranthus ruber

Abstract: Background: Predicting which alien species may become invasive is important in prioritising scarce resources for management. Objectives: Sixteen naturalised ornamentals in Cape Town were assessed for invasion potential in relation to a mechanistic framework. The recently spreading species, Centranthus ruber (L.) DC., was studied in detail following management actions and vegetation fires. Method: The mechanistic framework was developed using nine features most likely to promote invasiveness. Species were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The horticultural industry has been a particularly important pathway for the introduction of alien plants to South Africa, and the escape of ornamental plants from cultivation and gardens has resulted in some of the most extensive biological invasions in the country (Figs. 11.1b and 11.2b, c;Richardson et al 2003;Foxcroft et al 2008;Geerts et al 2013Geerts et al , 2017Holmes et al 2018).…”
Section: Plantsmentioning
confidence: 99%
“…The horticultural industry has been a particularly important pathway for the introduction of alien plants to South Africa, and the escape of ornamental plants from cultivation and gardens has resulted in some of the most extensive biological invasions in the country (Figs. 11.1b and 11.2b, c;Richardson et al 2003;Foxcroft et al 2008;Geerts et al 2013Geerts et al , 2017Holmes et al 2018).…”
Section: Plantsmentioning
confidence: 99%
“…5). Many widespread alien plants also seem to be confined to human-dominated ecosystems, for example Tree of Heaven (Ailanthus altissima; Walker et al 2017) and Red Valerian (Centranthus ruber; Geerts et al 2017;Holmes et al 2018). Urban areas provide important habitats for many other alien plants, and may act as beachheads for invasion into natural systems; they provide opportunities for species to accumulate high propagule pressure to drive invasions beyond the urban-wildland interface (e.g.…”
Section: Eco-evolutionary Experience and Biological Invasionsmentioning
confidence: 99%
“…Milton and Dean (2010) reported that seedlings of Pink Tamarisk (Tamarix ramosissima) occasionally recruited in large numbers following floods in dry riverbeds and dams. Prosopis species (Mesquite) in the Karoo appeared to spread substantially following large floods in 1970s and 1980s (Harding and Bate 1991), with a fourfold increase between 1974 and 1991 during above-average rainfall years (Hoffman et al 1995). Floods disperse Giant Reed (Arundo donax) rhizomes, which take advantage and establish in bare disturbed rivers, from where it rapidly invades (Guthrie 2007).…”
Section: Floodsmentioning
confidence: 99%